The influence of technology innovation adoption on customer perceived health risk and customer hotel selection behaviour during a pandemic period in Malaysia / Siti Nurul Iman Hajan and Nur Hidayah Che Ahmat - Iman Hajan, Siti Nurul; Che Ahmat, Nur Hidayah (Universiti Teknologi MARA, Perlis, 2023)
During the critical COVID-19 pandemic period, many governments, including the Malaysian government, imposed domestic and international travel bans. People were discouraged from travelling due to safety and regulations. The hotel industry was severely affected by the COVID-19 pandemic, and the government decision impacted the nature of hospitality services. Customers interacted face-to-face with hotel employees, thus increasing the possibility of being infected as the virus is primarily transmitted between human respiratory droplets and physical contact routes. Many hotels focused on improving their safety techniques and implementing risk-reduction strategies to encourage customers to visit their hotels. Some strategies include adopting technology innovation to minimise guest contact with hotel employees (e.g., contactless check-in and check-out) and improving cleanliness to minimise health risks (e.g., regularly sanitising hotel rooms and public areas). This study investigated the influence of technology innovation adoption on customers' perceived health risks and customers' hotel selection behaviour during the pandemic period in Malaysia. An online self-reported questionnaire was developed and conveniently distributed via social media platforms between December 2021 to February 2022. The data obtained showed that 420 individuals were interested in staying at four- or five-star hotels in Kuala Lumpur, Malaysia. Most of the respondents have had their second and third doses of vaccination. Based on the analysis, this study found that the adoption of technology innovation significantly influenced customer-perceived health risk and hotel selection behaviour. Findings from this study will benefit many stakeholders, such as hotel operators, and help them understand the influence of technology-based services on customer behaviour and in considering whether to invest in technology to maximise their businesses.